(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The viability of yoghurt and probiotic bacteria was assessed during production and storage for 35 days. Four commercial starter cultures were used in the yoghurt’s preparation. The titratable acidity, pH, and syneresis content portrayed similar patterns of increase and decrease from production to storage of the yoghurt. On the other hand, the percentage of syneresis showed an increase in cultures that contained L. delbrueckii ssp. bulgaricus. The viability of probiotic organisms during production and storage relied on the species and strain of associative yoghurt organisms present. The presence of L. delbrueckii ssp. bulgaricus impacted the viability of L. acidophilus, while thermophilic bacteria showed strong stability in yoghurt developed from cultures containing L. delbrueckii ssp. bulgaricus. The storage temperature of yoghurt affected the survival of the bulgaricus but not L. acidophilus. The variations in titratable acidity, pH, and syneresis were almost indistinguishable at storage temperatures of 4 and 10°C.